Presencia de Cochlodinium catenatum (Gymnodiniales: Gymnodiniaceae) en mareas rojas de Bahía de Banderas, Pacífico mexicano - Cortés Lara, María del Carmen (2004)
The evolution of an ichthiotoxic algal bloom caused by the dinoflagellate Cochlodinium catenatum was studied from July to December 2000. The abnormal multiplication of this dinoflagellate occurred in the form of a discoloration spreading between a temperature and salinity interval of 25-32°C and 33-35 ups, respectively. The density of C. catenatum reached 10 841 cells ml-1. The event was observed in large areas of Banderas Bay affecting 13 fish species, whose massive killing was due to suffocation (gill obstruction and excessive mucus production). The human population around the area did not present respiratory affections or skin irritation. The C. catenatum measurements suggest a hologamic and heterothalic reproduction. Their morphological characteristics suggest that C. polykrikoides, C. heterolobatum and C. catenatum are the same species. It is estimated that the species could be a recent introduction in the Mexican Pacific.